ONCOCYTIC ADRENOCORTICAL NEOPLASMS: A REPORT OF 10 CASES WITH EMPHASIS ON THE MALIGNANT SUBGROUP - Khoo, Serena SK; Challis, B; Marker, A; Shaw, A; Casey, R (Journal of the ASEAN Federation of Endocrine Societies, 2019)
*